2005
DOI: 10.1128/aac.49.3.1017-1022.2005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Transcriptional Activator RamA on Expression of Multidrug Efflux Pump AcrAB and Tigecycline Susceptibility in Klebsiella pneumoniae

Abstract: Tigecycline is an expanded broad-spectrum antibacterial agent that is active against many clinically relevant species of bacterial pathogens, including Klebsiella pneumoniae. The majority of K. pneumoniae isolates are fully susceptible to tigecycline; however, a few strains that have decreased susceptibility have been isolated. One isolate, G340 (for which the tigecycline MIC is 4 g/ml and which displays a multidrug resistance [MDR] phenotype), was selected for analysis of the mechanism for this decreased susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
138
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 21 publications
1
138
0
1
Order By: Relevance
“…A few AcrAB multidrug efflux systems have been characterized in Klebsiella spp. (7,20,23,28), but the sequencing data of K. pneumoniae strain MGH78578 show that many others potentially are present, as in closely related E. coli species (3). In this study, we characterized a gene cluster in K. pneumoniae LM21 that exhibits strong homologies with the EefABC RND efflux system-encoding operon, initially described in E. aerogenes (18).…”
Section: Discussionmentioning
confidence: 99%
“…A few AcrAB multidrug efflux systems have been characterized in Klebsiella spp. (7,20,23,28), but the sequencing data of K. pneumoniae strain MGH78578 show that many others potentially are present, as in closely related E. coli species (3). In this study, we characterized a gene cluster in K. pneumoniae LM21 that exhibits strong homologies with the EefABC RND efflux system-encoding operon, initially described in E. aerogenes (18).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that tigecycline resistance in K. pneumoniae is associated with the overexpression of the acrAB operon (26) (27) . Additionally, a study by Wang et al found there was a statistically significant linear trend in the expression of acrB as the tigecycline MIC increased (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mutations in these genes also influence the expression of acrAB (8). In K. pneumoniae and S. enterica, the expression of acrAB is governed by an additional global regulator, RamA (217,267). In Salmonella, field isolates carrying mutations in the regulatory region of ramRA or an insertion in soxR, increasing the expression levels of ramA and soxS, respectively, displayed increased resistance to fluoroquinolones (104).…”
Section: Mutational Resistance Related To Efflux Pumpsmentioning
confidence: 99%